Microbial biogeography of permafrost thaw ponds across the changing northern landscape. Issue 7 (25th August 2015) - Comte, Jérôme; Monier, Adam; Crevecoeur, Sophie; Lovejoy, Connie; Vincent, Warwick F.
Abstract : Microbial diversity varies at multiple spatial scales, but little is known about how climate change may influence this variation. Here we assessed the free‐living bacterioplankton composition of thaw ponds over a north‐south gradient of permafrost degradation in the eastern Canadian subarctic. Three nested spatial scales were compared: 1) among ponds within individual valleys 2) between two valleys within each landscape type, and 3) between landscape types (southern sporadic versus northern discontinuous permafrost). As a reference point, we sampled rock‐basin lakes whose formation was not related to permafrost thawing. β‐diversity was low at the smallest scale despite marked differences in limnological properties among neighboring ponds. β‐diversity was high among valleys, associated with greater environmental heterogeneity. The largest differences were between landscape types and appeared to reflect the concomitant effects of environmental filtering and dispersal limitation. Raup–Crick β‐diversity indicated that community assembly was driven by both stochastic (random extinction, dispersal, ecological drift) and deterministic (environmental filtering) processes. Communities sampled in the most degraded valley appeared primarily assembled through stochastic processes, while environmental filtering played a greater role at the other valleys. These results imply that climate warming and ongoing permafrost degradation will influence microbial community assembly, which in turn is likely to affect the functioning of thaw pond ecosystems.